Glycopolymer Code: Programming Synthetic Macromolecules for Biological Targeting - Yilmaz, Gokhan; Becer, Caglar Remzi (Macromolecular chemistry and physics, 2020)
Targeting in a cellular level is still one of the major challenges in biomedical treatments. However, new synthetic and analytical techniques now allow the development of precisely prepared macromolecules. Thus, glycopolymer chains are reported to be prepared with controlled length, monomer sequences, as well as chain‐folded structures. A high level of complexity in synthetic macromolecules also allows increased selectivity in targeting, which is a key factor in biomedical applications. Understanding the glycopolymer code is very crucial to design more suitable and functional glycopolymers for better approaches in biological and medical applications. When a great deal of interest in carbohydrate‐based systems is considered, it is not far from providing specific coding to glycopolymers.